2020
DOI: 10.1002/mrm.28498
|View full text |Cite
|
Sign up to set email alerts
|

QSM in canine model of acute cerebral ischemia: A pilot study

Abstract: In the present study, we investigated the potential of QSM to assess the physiological state of cortical tissue in the middle cerebral artery occlusion canine model of a cerebral ischemia. Methods: Experiments were performed in 8 anesthetized canines. Gradient echo, perfusion, and DWI data of brains at normal and ischemic states were acquired. In the postprocessed susceptibility and quantitative cerebral blood flow maps, changes in values within the middle cerebral artery-fed cortical territories were quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
2
2
0
Order By: Relevance
“…Compared to the contralateral hemisphere of the brain, an increase in magnetic susceptibility was seen in prominent cerebral vessels of injured regions in rodent brains with transient cerebral ischemia, and the regions of decreased susceptibility were observed at 24 h and 48 h after reperfusion, as reported previously [7]. In the subacute (1 day after stroke insult) phase of a canine model with pMCAO, increased susceptibility was detected in the infarct region of some animals in the study group with relatively high perfusion, while decreased susceptibility was found in the areas with decreased ADC and severe hypoperfusion in the other animals of the group [8]. As seen in the present study's monkey model of stroke, the magnetic susceptibility in the lesion area was significantly higher than that in the contralateral area during the hyperacute phase, which could be explained by increased oxygen extraction leading to higher concentrations of deoxyhemoglobin in the veins, as reported in a previous QSM study of stroke rodents [7].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Compared to the contralateral hemisphere of the brain, an increase in magnetic susceptibility was seen in prominent cerebral vessels of injured regions in rodent brains with transient cerebral ischemia, and the regions of decreased susceptibility were observed at 24 h and 48 h after reperfusion, as reported previously [7]. In the subacute (1 day after stroke insult) phase of a canine model with pMCAO, increased susceptibility was detected in the infarct region of some animals in the study group with relatively high perfusion, while decreased susceptibility was found in the areas with decreased ADC and severe hypoperfusion in the other animals of the group [8]. As seen in the present study's monkey model of stroke, the magnetic susceptibility in the lesion area was significantly higher than that in the contralateral area during the hyperacute phase, which could be explained by increased oxygen extraction leading to higher concentrations of deoxyhemoglobin in the veins, as reported in a previous QSM study of stroke rodents [7].…”
Section: Discussionsupporting
confidence: 85%
“…QSM changes in ischemic brains have been reported previously in studies of acute stroke animal models [7,8] and patients [31]. Compared to the contralateral hemisphere of the brain, an increase in magnetic susceptibility was seen in prominent cerebral vessels of injured regions in rodent brains with transient cerebral ischemia, and the regions of decreased susceptibility were observed at 24 h and 48 h after reperfusion, as reported previously [7].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…There is a growing body of work on the application of QSM in cerebral ischemia in both preclinical models and patients. [39][40][41][42][43][44] In the present study we used QSM to measure changes in the magnetic susceptibility of venous blood across a range of oxygenation states. While the linear relation between the concentration of deoxyhemoglobin and venous susceptibility has been previously reported, [16][17][18][19] ours is the first study to report a direct relationship between venous susceptibility and brain tissue PO 2 .…”
Section: Discussionmentioning
confidence: 99%